Quantifying the reflective index of nanometer-thick thiolated molecular layers on nanoparticles. Issue 6 (25th January 2017) - Lin, Li; Liu, Zhonghui; Li, Xiyao; Gu, Hongchen; Ye, Jian
Abstract : A method to quantify the reflective index of nanometer-thick thiolated molecular layers on gold nanoparticles (NPs) is developed by measuring and calculating the localized surface plasmon resonance shift of NPs and by examining the molecular layer thickness via the TEM visualization of nanogaps in core–shell particles. Abstract : To precisely measure the refractive index (RI) of molecular layers is of great help to understand their fundamental optical properties and to develop advanced molecular layer-based devices including biosensors, photodetectors, and metamaterials. However, accurate quantification of the RI of ultra-thin nanometer-thick molecular layers immobilized on the surface of aqueous nanoparticles (NPs) remains a challenge. Here we have developed a method to quantify the effective RI of ultra-thin thiolated molecular layers with a thickness down to a sub-nanometer scale on the surface of plasmonic gold (Au) NPs. This method is realized by measuring and calculating the localized surface plasmon resonance (LSPR) shift of NPs due to the change of the surrounding RI and by quantifying the accurate molecular layer thickness via the TEM visualization of a nanogap junction in core–shell nanomatryoshka particles. The effective RI of the molecular layer is determined by fitting the experimental and calculated LSPR shifts using the least squares method. We have applied this method to quantify the effective RI of 1, 4-benzenedithiol, 4, 4′-biphenyldithiol, and 4, 4′-terpheyldithiol molecules, proving their effectiveness and feasibility in ultra-thin molecular layers adsorbed on the NPs.